FAKE NEWS, MISINFORMATION AND DISINFORMATION ABOUT COVID-19 IN SOCIAL MEDIA DURING THE PANDEMIC AND POST-PANDEMIC TIME (CASE OF GEORGIA) - Osepashvili, Dali (International Journal of Innovative Technologies in Social Science, 2023)
Spreading fake news and disinformation is one of the global challenges over the last years. It is a challenge for Georgia too. This acute problem was also current at the beginning of the Covid-19 pandemic, when a number of misinformation appear in the social media as well as in the traditional media, regarding the origin and spread of the coronavirus, especially in Facebook which is the most popular social network in Georgia. A lot of fake news was spread and is still being spread in the post-pandemic period too. The Goal of this research paper is to explore the attitudes of Georgian Facebook users, specifically what kind of fake news and disinformation they met about Coronavirus in social media, how to identify them, how much they tried to verify them, how to explain their spread, how to fight them, etc. In order to explore this issue a social constructivism framework is used. As for the main research method, this study is based on the qualitative approach. For this purpose, the method of in-depth interviews - with Georgian active internet users – has been conducted. The respondents are doctors, journalists as well as representatives of different academic fields, who possess media literacy skills.